Descubrir el patrimonio inmaterial a través de la creación de narrativas digitales con Scratch - Rubio-Navarro, Gabriel (Huarte de San Juan. Filología y Didáctica de la Lengua, 2016)
The Archive of the Intangible Heritage of Navarre hosts numerous graphics, text and sound elements that build a huge media database for research and knowledge about the cultural richness of Navarre and Lower Navarre. This database, still, maintains a certain distance from its target audience: students of primary and secondary schools. The paper describes the design of a teaching strategy based on digital storytelling and transmedia, capable of building bridges with this target. To do this, the profile of the students, the school environment and the digital context in which they live will be analyzed first. Then the relationship of intangible heritage and digital storytelling will be studied, including the technical and educational needs in order to develop this line of work with the programming tool of video games and interactive stories Scratch (MIT).